Impact of time from blood specimens collection to centrifugation on the diagnosis of gestational diabetes mellitus - Binbin Yin; Yongying Bai; Jinghua Zhang; Yan Zhang; Xia Li; Yue Jin; Xinyi Mou; Kexin Fang; Yan Chen; Yue Cheng; Bo Zhu (Annals of Medicine)
Objective The process of glycolysis from blood collection to centrifugation impacts the diagnosis of gestational diabetes mellitus (GDM). However, the specific characteristics of the working environment in China and its influence on GDM diagnosis still need to be clarified.Methods Firstly, 15 pregnant women were recruited, and six specimens were collected from each in a fasting state. The specimens were left at room temperature for different times (0.5, 1, 2, 3, 4, and 5 h) and then centrifuged. Subsequently, data were collected from pregnant women who underwent oral glucose tolerance test (OGTT) between June 1, 2021, and July 30, 2022. Pregnant women were categorized into different groups based on different pre-treatment times, and the incidence of GDM was calculated for each group.Results Glucose levels gradually decreased as the specimen remained longer before centrifugation, a decrease of 1.15 mmol/L (27.58%) from the initial glucose level (3.02 ± 0.30 mmol/L VS. 4.17 ± 0.28 mmol/L, p < 0.001). 2-h specimens had the longest pre-treatment time (29.92 ± 14.94 min (min)), accounting for half of the specimens exceeding 90 min. The longer the specimen pre-treatment time, the greater the impact on the diagnosis of GDM. Timely centrifugation prevented 3.42%, 3.35%, and 2.21% missed GDM diagnoses.Conclusions In the Chinese healthcare environment, prolonging specimen pre-treatment time can affect GDM diagnosis. Therefore, standardizing specimen pre-treatment is crucial to minimize potential effects.